Cannabis use and mental health-related quality of life among individuals with depressive disorders. Issue 2 (15th December 2015) - Aspis, Itay; Feingold, Daniel; Weiser, Mark; Rehm, Jurgen; Shoval, Gal; Lev-Ran, Shaul
Abstract: Cannabis is the most widely used illicit substance among individuals with depressive disorders. This study aimed to evaluate whether among individuals with depressive disorders, higher frequency of cannabis use would be associated with poorer Quality of Life (QoL), based on a large nationally representative US sample. Individuals with depressive disorders ( N =3416) were divided into categories according to no use ( N =3096), occasional use (less than weekly, N =176) and regular (at least weekly, N =144) use of cannabis in the past 12 months. QoL was assessed using the Short-Form 12 (SF-12) questionnaire. Women who used cannabis regularly had a significantly lower SF-12 Mental Component Summary score (MCS) compared to non-users, with a mean difference of 0.4 Standard Deviations (SDs). Comparison of subscale scores showed no significant differences. No significant difference was noted when comparing women who used cannabis occasionally to non-users. No differences were found among men when comparing MCS and mental subscale scores of both regular and occasional users to non-users. Our findings highlight the importance of taking gender and the frequency of cannabis use into account, when assessing functional and emotional aspects of cannabis use among individuals with depressive disorders. Highlights: We examined the association between frequency of cannabis use and mental Quality of Life among individuals with Depressive disorders. Regular, but not occasional, cannabis use, was found to be associated with decreased mental Quality of Life among women with depressive disorders. Cannabis use was not found to be associated with differences in Quality of Life among men with depressive disorders, regardless of frequency. Gender and frequency of cannabis use are important variables when assessing functional and emotional aspects of cannabis use in depression.